Penjadwalan Ulang Penerbangan Pesawat Boeing 737-800NG PT. Lion Mentari Airlines di Bandara Soe-Ta Dengan Metode Hungarian - Hardono, Joko; Hidayat, Dian Friana; Wicaksono, Abdul Galih (Journal Industrial Manufacturing, 2023)
The Covid-19 outbreak that has spread throughout the world has resulted in a significant reduction in the number of users of the aircraft mode of transportation. The decline in the number of passengers was also experienced by PT. Lion Mentari Airlines or often known as Lion Air. This of course will have an impact on decreasing the company's revenue thereby reducing the Company's ability to pay for the rental costs of several of its aircraft. It is necessary to reschedule aircraft flights to increase aircraft optimization so that existing passenger services can be met with a smaller number of aircraft compared to before the Covid-19 pandemic. Flight scheduling at Lion Air is based on market demand, aircraft maintenance programs, aircraft availability per day and airport operating hours. This research will reschedule Lion Air flight paths on Boeing 737-800NG aircraft during the Covid-19 pandemic based on airport waiting time / ground time using the Hungarian method. The waiting time at Soekarno-Hatta airport before optimization was 5,895 minutes and there was a significant decrease in waiting time at Soekarno-Hatta airport after optimization, which was 18.78% or 1,107 minutes to 4,788 minutes, and by using the new schedule, Lion Air, which was originally operating 7 aircraft fleets for these flight routes can be optimized using only 6 aircraft fleets. Keywords: Operations Research, Assignment Problems, Hungarian Method, Boeing 737-800NG, Covid-19